An elucidation of selected pre-harvest practices and postharvest treatment influencing 'Hass' avocado fruit exocarp colour development during ripening - Shikwambana, Kingsly (My University, 2022)
In 'Hass' avocado fruit, pre-harvest and postharvest factors affecting exocarp colour change during ripening are vital to maintain the industry’s credibility, competitiveness and profitability. Currently, the South African ‘Hass’ avocado fruit exocarp colour development is affected by pre- and postharvest factors, ultimately, fruit does not develop the required purple colour during ripening. These pre- and postharvest factors must be understood in order to implement strategies that avoid downgrading of South African 'Hass' avocado fruit by lucrative markets due to insufficient purple colour development during ripening. In 'Hass' avocado fruit, exocarp colour development is associated with an increase in anthocyanin synthesis and accumulation during ripening. However, limited information is available regarding factors regulating anthocyanin synthesis and accumulation in 'Hass' avocado fruit during ripening. Therefore, the overall aims of this study were to investigate pre-harvest practices and postharvest treatment that increase exocarp anthocyanin synthesis during ripening. In addition, determine whether exocarp glucose and other antioxidants contribute to 'Hass' avocado fruit exocarp colour development during ripening. In chapter 3, the study looked at how crop load adjustment affects ‘Hass’ avocado fruit exocarp colour development during ripening at three different harvest maturities. The crop load adjustment treatments were applied as: high (100%), moderate (50%) and low (25%) at three harvest times (early, mid- and late). After harvest, fruit were stored at 5.5°C for 28 days, thereafter, ripened at 25°C. The experimental design was carried out as 3 x 3 factorial, arranged in a completely randomized design (CRD) with three replications. The results showed that total anthocyanin and cyanidin 3-O-glucoside concentrations of ‘Hass’ avocados increased following crop load adjustment from normal (100%) to moderate (50%) and low (25%) loads, resulting in improved exocarp colour development during ripening. Furthermore, we discovered that fruit harvested from moderate (50%) and low (25%) crop loads accumulated higher exocarp sugars (D-mannoheptulose and perseitol) at three harvest maturities when compared with high crop load (100%). Moreover, total phenolic concentration of fruit harvested from moderate (50%) and low (25%) crop loads was higher than that obtained from high load fruits, irrespective of harvest maturities. In chapter 4, the study examined the interaction between branch girdling and harvest maturation on the development of 'Hass' avocado fruit exocarp colour during ripening. The experimental design was carried out as 2 x 2 factorial, arranged in a completely randomized design (CRD). The results showed that fruit harvested from girdled trees had poor exocarp colour development as compared to fruit harvested from control trees, regardless of harvest time. Fruit harvested from girdled and ungirdled avocado trees did not show significant differences in visual exocarp colour during early and mid-maturity. Apart from crop load adjustment and girdling as pre-harvest methods to manipulate postharvest exocarp colour, glucose was also infused through the pedicel. Studies on the effect of glucose infusion through the pedicel on the exocarp colour of the ‘Hass’ avocado fruit during ripening were presented in chapter 5. The study included five treatments; control fruit with pedicel and infused with distilled water and glucose concentrations (0.05, 0.13 and 0.28 mM). The distilled water, glucose infused and control fruit were stored at 5.5°C for up to 28 days. After cold storage, fruit were kept at ambient temperature 25°C for ripening. The experiment was conducted as a completely randomized design (CRD) with three replications per treatment. The results showed that glucose infusion through the pedicel markedly increased anthocyanin and cyanidin 3-O-glucoside concentration during ripening. Interestingly, glucose concentrations (0.05 and 0.13 mM) resulted in purple colour development after 8 days at 25°C when compared with control, distilled water and highest concentration (0.28 mM). In chapter 6, the relationship between 'Hass' avocado fruit size, exocarp colour and related pigments with antioxidants capacity and sugar concentration during ripening were investigated. The fruit were categorized by their weight; small (< 200 g) and large (> 201 g). Their diameter and length were also measured using a vernier calliper. Fruit ware stored at 5.5°C for 28 days, then ripened at 25°C. The experimental design was carried out as a completely randomised design (CRD), using 25 fruit replications per category. The results showed that small-sized fruit developed the desirable purple to black exocarp colour when compared with large-sized fruit. Additionally, the results showed that small-sized fruit had higher antioxidant capacity as measured by 2,2 diphenyl 1 picrylhydrazyl (DPPH), ascorbic acid and flavonoid content during ripening when compared with large-sized fruit. Furthermore, it was found that small-sized fruit accumulated higher exocarp and seeds (D-mannoheptulose, perseitol, sucrose and glucose) sugar concentration. We demonstrated and concluded that exocarp colour, pigments, antioxidants and sugar concentration are closely related to size in 'Hass' avocado fruit. Knowledge from this thesis contributes toward the understanding of pre and postharvest factors that may influence colour development of ‘Hass’ avocado fruit during ripening. This study contributes towards bridging the gap in the literature on the biochemical changes associated with colour development of ‘Hass’ avocado fruit during ripening
Thesis (Ph.D. (Plant Production)) -- University of Limpopo, 2022
Keywords: ‘Hass’; Avocado fruit; Postharvest; Fruit -- Ripening; Avocado; Fruit -- Color; Avocado industry